THE ROLE OF REVERSE LOGISTICS IN SUSTAINABLE AGRICULTURE: THE ROLE OF REVERSE LOGISTICS IN SUSTAINABLE AGRICULTURE - Antonov, Anton (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Reverse logistics is emerging as a key mechanism for implementing a circular economy and sustainable agriculture in the face of economic, social, and environmental challenges in the agricultural sector. This report analyzes the conceptual foundations of reverse logistics, its specifics, and its application in sustainable agriculture.